Conservatism and innovation in the Hebrew language of the Hellenistic period proceedings of a fourth International Symposium on the Hebrew of the Dead Sea Scrolls & Ben Sira - International Symposium on the Hebrew of the Dead Sea Scrolls and Ben Sira; Joosten, Jan 1959-; Rey, Jean-Sébastien 1974- (Leiden Boston Brill, 2008)
This volume contains 15 contributions addressing linguistic and philological issues. They seek to relate the Hebrew texts of the Hellenistic period to both earlier and later traditions. The papers deal with the Qumran scrolls, the Apocrypha and the Hebrew Bible
Includes bibliographical references and indexes. - Contributions in English and French. - Description based on print version record
Online-Ausg.
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Sirach; Dead Sea Scrolls -- Congresses; Bible -- Congresses -- Language, style -- Qumrantexte; Dead Sea Scrolls -- Congresses; Bible -- Language, style -- Congresses; Dead Sea Scrolls -- Congresses -- Congresses -- Language, style; Bible. Apocrypha. Ecclesiasticus -- Congresses -- Congresses -- Language, style; Qumrantexte; Dead Sea Scrolls; Bible; Hebrew language, Post-Biblical -- Congresses -- Hebräisch; Hebrew language, Post-Biblical -- Congresses; FOREIGN LANGUAGE STUDY ; Hebrew; Hebrew language, Post-Biblical; Frühjudentum; Conference papers and proceedings; Hebräisch; Electronic books; Konferenzschrift